2015
DOI: 10.1099/mic.0.000007
|View full text |Cite
|
Sign up to set email alerts
|

Sortase-deficient lactobacilli: effect on immunomodulation and gut retention

Abstract: Surface proteins of probiotic microbes, including Lactobacillus acidophilus and Lactobacillus gasseri, are believed to promote retention in the gut and mediate host-bacterial communications. Sortase, an enzyme that covalently couples a subset of extracellular proteins containing an LPXTG motif to the cell surface, is of particular interest in characterizing bacterial adherence and communication with the mucosal immune system. A sortase gene, srtA, was identified in L. acidophilus NCFM (LBA1244) and L. gasseri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 39 publications
(43 reference statements)
0
42
0
Order By: Relevance
“…In vitro bacterial-DC co-incubation assays were performed as described previously (Johnson et al, 2013; Call et al, 2015). Cytokine measurements for IL-6, IL-10, and IL-12 were quantified using Single-Analyte ELISArray kits (Qiagen), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro bacterial-DC co-incubation assays were performed as described previously (Johnson et al, 2013; Call et al, 2015). Cytokine measurements for IL-6, IL-10, and IL-12 were quantified using Single-Analyte ELISArray kits (Qiagen), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…For L. acidophilus NCFM, the specificity of probiotic activity on the host has been characterized for numerous cell surface components, including lipoteichoic acid (Mohamadzadeh et al, 2011), sortase-dependent proteins (Call et al, 2015), an aggregation promoting factor (Goh and Klaenhammer, 2010), and a myosin-cross reactive protein (O’Flaherty and Klaenhammer, 2010b). Proteins at the Surface (S-) layer, which are non-covalently bound to the apical component of the cell wall peptidoglycan, are also of interest to the understanding of microbe-host interactions (Hynönen and Palva, 2013; Johnson and Klaenhammer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these approaches have been extensively applied to investigate cell-surface constituents, as they are highly strain-specific and are uniquely positioned to effect host–microbe crosstalk (Buck et al, 2005; Kleerebezem et al, 2010). Predictive and functional genomics studies of L. acidophilus NCFM have revealed that surface layer (Slps) and surface layer associated proteins (SLAPs) (Buck et al, 2005; Johnson et al, 2013), sortase-dependent proteins (Call et al, 2015), and adhesion exoproteins mediate adhesion and immunomodulatory activities of L. acidophilus (Buck et al, 2005). L. acidophilus synthesizes three Slps, the dominant SlpA and minor components SlpB and SlpX (Goh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, the probiotic activity of L. acidophilus is mediated by cell surface-associated components which interact with the host gastrointestinal mucosa and immune system (911). …”
Section: Introductionmentioning
confidence: 99%